2020
DOI: 10.1111/cogs.12895
|View full text |Cite
|
Sign up to set email alerts
|

Adding Types, But Not Tokens, Affects Property Induction

Abstract: The extent to which we generalize a novel property from a sample of familiar instances to novel instances depends on the sample composition. Previous property induction experiments have only used samples consisting of novel types (unique entities). Because real‐world evidence samples often contain redundant tokens (repetitions of the same entity), we studied the effects on property induction of adding types and tokens to an observed sample. In Experiments 1–3, we presented participants with a sample of birds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…As with strong sampling, we therefore would expect tighter generalization with increasing data under conditions of property sampling. The predicted differences in the tightening of generalization under strong and weak sampling assumptions have been observed across of range of single-category learning and property inference tasks (e.g., Hayes, Banner, Forrester, et al, 2019;Hendrickson et al, 2019;Ransom et al, 2018;Ransom et al, 2016;Xie et al, 2020). Likewise, the predicted differences between property generalization under property and category sampling have also been demonstrated in property inference (Hayes, Banner, Forrester, et al, 2019).…”
Section: Formalizing Sampling Assumptionsmentioning
confidence: 83%
“…As with strong sampling, we therefore would expect tighter generalization with increasing data under conditions of property sampling. The predicted differences in the tightening of generalization under strong and weak sampling assumptions have been observed across of range of single-category learning and property inference tasks (e.g., Hayes, Banner, Forrester, et al, 2019;Hendrickson et al, 2019;Ransom et al, 2018;Ransom et al, 2016;Xie et al, 2020). Likewise, the predicted differences between property generalization under property and category sampling have also been demonstrated in property inference (Hayes, Banner, Forrester, et al, 2019).…”
Section: Formalizing Sampling Assumptionsmentioning
confidence: 83%
“…However, we note that other studies have shown that repetition can increase the memorability of a claim without necessarily increasing confidence in its accuracy (Xie et al, 2020).…”
Section: False Consensus and Source Reliability 30mentioning
confidence: 55%
“…This is important because the strength of generalisation should be monotonically related to the amount of positive evidence observed (i.e., the monotonicity principle; Osherson et al, 1990). Although monotonicity might, in principle, be able to account for the results in Experiment 1, it is worth noting that in other induction and category learning tasks, participants sometimes interpret repetitions of the same instance as separate instances (Barsalou, Huttenlocher, & Lamberts, 1998;Xie, Hayes, & Navarro, 2018). Nonetheless, it was important to ensure that any group differences found in our predictive learning task could be attributed to diversity and not monotonicity.…”
Section: Methodsmentioning
confidence: 99%